Penerapan Analytical Hierarchy Proccess, Clustering, dan AR-MBA sebagai Solusi Strategi Pemasaran Pada Toko Swalayan X - Magister Kalijaga (Inovbook, 2021)
People in every area are now spoiled by the presence of various shopping centers. The location of shopping places which are currently close to each other makes an advantage for the community because they can freely choose which shopping area to go to. The purpose of this research is to create a marketing strategy that is carried out using decision analysis and data mining (AKDM). In addition to knowing the level of overall sales and product sales, decision analysis and data mining are also used to determine the pattern of purchasing goods by consumers. So that a strategy can be designed to attract customers and win the market. The methods used in this study are AHP, Clustering, and AR-MBA. It is known based on data processing that the products that are often purchased are chitato, taro, etc. The type of drink is cocacola, fanta, yakult, etc. In addition, there were 4 patterns of customer purchases (Dept. 6 and Dept. 2, Dept. 9 and Dept. 4, Dept. 9 and Dept. 2, Dept. 7 and Dept. 2). The strategy that can be applied by considering the results of data processing is to promote the mix between products.